Chemistry of Volatile Organic Compounds in the Los Angeles basin: Nighttime Removal of Alkenes and Determination of Emission Ratios. Issue 21 (2nd November 2017) - de Gouw, J. A.; Gilman, J. B.; Kim, S.‐W.; Lerner, B. M.; Isaacman‐VanWertz, G.; McDonald, B. C.; Warneke, C.; Kuster, W. C.; Lefer, B. L.; Griffith, S. M.; Dusanter, S.; Stevens, P. S.; et al.
Abstract: We reanalyze a data set of hydrocarbons in ambient air obtained by gas chromatography‐mass spectrometry at a surface site in Pasadena in the Los Angeles basin during the NOAA California Nexus study in 2010. The number of hydrocarbon compounds quantified from the chromatograms is expanded through the use of new peak‐fitting data analysis software. We also reexamine hydrocarbon removal processes. For alkanes, small alkenes, and aromatics, the removal is determined by the reaction with hydroxyl (OH) radicals. For several highly reactive alkenes, the nighttime removal by ozone and nitrate (NO3 ) radicals is also significant. We discuss how this nighttime removal affects the determination of emission ratios versus carbon monoxide (CO) and show that previous estimates based on nighttime correlations with CO were too low. We analyze model output from the Weather Research and Forecasting‐Chemistry model for hydrocarbons and radicals at the Pasadena location to evaluate our methods for determining emission ratios from the measurements. We find that our methods agree with the modeled emission ratios for the domain centered on Pasadena and that the modeled emission ratios vary by 23% across the wider South Coast basin. We compare the alkene emission ratios with published results from ambient measurements and from tunnel and dynamometer studies of motor vehicle emissions. We find that with few exceptions the composition of alkene emissions determined from the measurements in Pasadena closely resembles that of motor vehicle emissions. Plain Language Summary: We report new measurements of hydrocarbons in ambient air in the Los Angeles basin. Chemical reactions between hydrocarbons and nitrogen oxides form ozone and fine particles, two important pollutants in Los Angeles smog. It is therefore important to understand hydrocarbon emission sources. In this work, we derive the composition of hydrocarbon emissions using ambient measurements at Pasadena in 2010. The study is complicated due to rapid chemical reactions that remove hydrocarbons in between the time of emission and measurement. After correcting for this chemistry, it is shown that the composition of reactive alkenes agrees closely with those emitted from motor vehicles. Key Points: An expanded data set of hydrocarbons in ambient air in the Los Angeles basin is presented and analyzed For reactive alkenes, removal by ozone and nitrate radicals at night is important in addition to their removal by hydroxyl radicals during the day, which complicates determining the composition of emissions After correction for chemical removal, the composition of reactive alkene emissions is consistent with a source from motor vehicles